Forecasting the Patterns and Trends in Age-Specific Fertility in South Asia - et. al., Nasriyah Arbu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The total fertility rate (TFR) in South Asia has decreased remarkably over the past three decades. The decline is projected to continue in the coming years mostly due to the significant changes occurring in age specific fertility rate (ASFR). This study aims to investigate ASFR trends and forecast the ASFR of India, Bangladesh, and Pakistan from 2020 to 2100. The ASFRs in South Asia data separated by 7 age groups with 5-year interval from 15 to 49 years between 1990 and 2019 were downloaded from the US Census Bureau’s website. Linear regression models were used to investigate ASFR patterns from data in that period and ASFR data in the years 2010-2019 of each age group were used to forecast the ASFRs in 2020 to 2100. The forecasted results show that ASFRs in India and Bangladesh in age group 15-24 years have steep declining trends whereas ASFRs in age group 25-29 in both countries and age group 45-49 years in India have gradually decreasing ASFR trends. Age group 30-44 years in Bangladesh have slightly decreasing ASFR trends. Pakistan with previously high fertility rates are experiencing gradually declining ASFRs in all age groups. In conclusion, the change in fertility in these three countries from low stable population to high population will occur within next 40 years from 2020